2020
DOI: 10.33774/apsa-2020-jf671
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Democracy, State Capacity, and COVID-19 Related School Closures

Abstract: This paper provides a preliminary analysis of the institutional determinants of the timing of COVID-19 related school closures, focusing on the role of democracy and administrative state capacity. To this end, the paper reports a set of survival analyses of school closures around the world in February and March of 2020. Relying foremost on an analysis of the number of days to school closure after the day of the 10th confirmed case of COVID-19 in 134 countries, the paper finds that other things being equal, dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(37 citation statements)
references
References 0 publications
1
36
0
Order By: Relevance
“…Tracking data from smartphones, research has also shown similar partisan divides among individuals: areas of the United States with more Republicans practice less social distancing (Allcott et al, 2020;Barrios and Hochberg, 2020). In a cross-country context, Cronert (2020) show that more democratic governments were faster to shut down schools, though governments with higher state capacity were slower to do so. Our analysis, by contrast, focuses on the number of per capita deaths related to COVID-19 in the early stages of the pandemic.…”
Section: Introductionmentioning
confidence: 93%
“…Tracking data from smartphones, research has also shown similar partisan divides among individuals: areas of the United States with more Republicans practice less social distancing (Allcott et al, 2020;Barrios and Hochberg, 2020). In a cross-country context, Cronert (2020) show that more democratic governments were faster to shut down schools, though governments with higher state capacity were slower to do so. Our analysis, by contrast, focuses on the number of per capita deaths related to COVID-19 in the early stages of the pandemic.…”
Section: Introductionmentioning
confidence: 93%
“…Interestingly, those with high government effectiveness were slower to implement such policies [36] as were the more right-leaning governments [37]. Further, more democratic countries have tended to be more sensitive to the domestic policy decisions of other countries [38].…”
Section: Politicalmentioning
confidence: 99%
“…Further, more democratic countries have tended to be more sensitive to the domestic policy decisions of other countries [38]. Regardless, the need to understand the reasons behind the selection of some policy instruments and not others [36] and the associated timing of such decisions is warranted to enable the development and implementation of more appropriate policy…”
Section: Politicalmentioning
confidence: 99%
“…[25][26][27][28] ), when they decided to implement them 29,30 , who they were targeted towards 31,32 and what state capacity they possessed to do so 33,34 have all significantly influenced how the virus has affected health outcomes both within and across different country contexts [35][36][37] , all of which are readily captured by this dataset 38,39 . Equally important is understanding why countries adopt different policies, with early analyses suggesting that institutional and political factors, for example, the authoritarian or democratic nature of the institutions of a country 40 or its level of political partisanship 41 , play an important role. These findings will not only help improve the global response to the current crisis but can also build an influential foundation of knowledge for responding to future outbreaks 42,43 .…”
mentioning
confidence: 99%